Teaching points-do they occur and what do they contain? An observation study concerning the general practice rotation. Issue 1 (December 2016) - Duncan, Gertrude; Roth, Lisa; Donner-Banzhoff, Nobert; Boesner, Stefan
Abstract Background A general practice rotation is mandatory in most undergraduate medical education programs. However, little is known about the student-teacher interaction which takes place in this setting. In this study we analyzed occurrence and content of teaching points. Methods From April to December 2012, 410 individual patient consultations were observed in twelve teaching practices associated with the Philipps University Marburg, Germany. Material was collected using structured field-note forms and videotaping. Data analysis was descriptive in form. A teaching point is defined here as a general rule or specific, case–related information divulged by the teaching practitioner. Results According to the analysis of 410 consultations, teaching points were made in 66.3 % of consultations. During these consultations, 74.3 % general- and 46.3 % case related teaching points occurred; multiple categorizations were possible. Of seven possible topics, therapy was most common, followed, in frequency of occurrence, by patient history, diagnostic procedure, physical examination, disease pathology, differential diagnosis, risk factors and case presentation. Conclusions The majority of consultations conducted within student presence contained teaching points, most frequently concerning therapy. General teaching points were more common than specific teaching points. Whilst it is encouraging that most consultations included teaching points, faculty development aimed at raising awareness for teaching and learning techniques is important.